1998
DOI: 10.1212/wnl.50.1.114
|View full text |Cite
|
Sign up to set email alerts
|

The functional neuroanatomy of tinnitus

Abstract: We used PET to map brain regions responding to changes in tinnitus loudness in four patients who could alter tinnitus loudness by performing voluntary oral facial movements (OFMs). Cerebral blood flow was measured in four patients and six controls at rest, during the OFM, and during stimulation with pure tones. OFM-induced loudness changes affected the auditory cortex contralateral to the ear in which tinnitus was perceived, whereas unilateral cochlear stimulation caused bilateral effects, suggesting a retroco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
326
3
12

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 555 publications
(363 citation statements)
references
References 10 publications
14
326
3
12
Order By: Relevance
“…Tinnitus would reflect an integrated interneuronal neurotransmission pathway including the frontal, temporal, and parietal lobes, thalamus, and cerebellum (Shulman, 2005). A major hypothesis on the pathophysiological mechanisms is that tinnitus would involve a lesion leading to deafferentation of excitatory inputs on thalamic relay cells (Tonndorf, 1987;Moller, 1997;Lockwood et al, 1998). This would lead to a thalamic deactivation (Llinás et al, 2005), disrupting in turn thalamo-cortical interactions (Jeanmonod et al, 1996;Llinás et al, 1999), and leading to the appearance of tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…Tinnitus would reflect an integrated interneuronal neurotransmission pathway including the frontal, temporal, and parietal lobes, thalamus, and cerebellum (Shulman, 2005). A major hypothesis on the pathophysiological mechanisms is that tinnitus would involve a lesion leading to deafferentation of excitatory inputs on thalamic relay cells (Tonndorf, 1987;Moller, 1997;Lockwood et al, 1998). This would lead to a thalamic deactivation (Llinás et al, 2005), disrupting in turn thalamo-cortical interactions (Jeanmonod et al, 1996;Llinás et al, 1999), and leading to the appearance of tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…An early study using PET reported more extensive auditory cortical activation in response to a 2-kHz tone in a group of four TI patients with mild-to-moderate hearing loss (>2 kHz from 30 to 70 dB) compared to controls with hearing levels of 25 dB or better from 0.25 to 8 kHz (Lockwood et al, 1998). While 2 kHz corresponded to the edge of the hearing loss, the TI pitch was matched near the peak of hearing loss, not the lesion edge.…”
Section: Human Neuroimaging Studiesmentioning
confidence: 98%
“…Instead we illustrate some of the neural changes that occur in higher centres of the auditory system that receive inputs from the dorsal cochlear nucleus. Lockwood et al (1998) studied four patients with high-frequency hearing loss who were able to control the loudness of their troublesome TI by performing an oral facial movement. In two patients, the movement decreased TI loudness and this specifically reduced activity in the left primary and nonprimary auditory cortex, contralateral to the TI percept.…”
Section: Voluntary Modulation Of Ti By Somatomotor Movementsmentioning
confidence: 99%
“…Finally, excellent critical literature summaries on the neurobiology of tinnitus have emerged which detail the aspects touched upon below (e.g. Baguley, 2002;Bauer, 2004;Eggermont, 2005;Eggermont & Roberts, 2004;Kaltenbach, 2006;Kaltenbach, Zhang, & Afman, 2000;Lockwood et al, 1998Lockwood et al, , 2005Møller, 2006;Salvi, Lockwood, & Burkard, 2000).…”
Section: Tinnitus Backgroundmentioning
confidence: 99%
“…These methods have been applied with success in human tinnitus patients to identify various brain areas active during phantom perceptions, and to examine the effects of some treatments (see for example Giraud et al, 1999;Mirz et al, 1999;Reyes et al, 2002). There is now good evidence from PET and magnetic encephalography that a reorganization of the frequency axis in the human auditory cortex occurs much as described above (Lockwood et al, 1998;Mühlnickel et al, 1998). Nevertheless, a more recent study using neuromagnetic recordings (this permitted identification of highly specific brain locations) suggested that equivalent dipole activity at the edge of hearing loss was no more active than control locations (Weisz, Wienburch, Dohrmann, & Elbert, 2005).…”
Section: Cortical Reorganization and Tinnitusmentioning
confidence: 99%